Manufacture of a flying robot propeller made from plant-based composite material derived from snake plant (Sansevieria trifasciata) fibers. - Arsyad Mulya Rahman; Syaifa Mulyadi; Hanalde Andre; Denisa Rahmi Syaifani (METAL: Jurnal Sistem Mekanik dan Termal, 2026)
The development of flying robot technology or Unmanned Aerial Vehicles (UAVs) requires innovations in materials that are lightweight, strong, and environmentally friendly. This study aims to design and manufacture flying robot propellers using composite materials with an epoxy resin matrix reinforced with natural fibers from snake plants (Sansevieria trifasciata). Sansevieria trifasciata fibers were chosen for their potential as an alternative material with good specific strength, abundant availability, and light weight. The propeller was manufactured using the hand lay-up method, followed by mechanical testing to determine the characteristics of the composite material, including tensile and impact tests. In addition, functional testing was conducted to measure the performance of the propeller in generating thrust. The results of the study show that Sansevieria trifasciata fiber composites have sufficient mechanical properties to be used as propeller materials for small-scale UAVs. The thrust performance produced is comparable to that of similar commercial propellers, indicating that natural fibers can replace conventional synthetic fiber-based materials and support more sustainable technological advances.